Molecular modelling of a pathogenesis related protein from Solanum tuberosum - Thakur, S; Sur, S; Bose, D; Goyal, AK; Mishra, T; Rai, R; Bhattacharya, M; Bothra, AK; Sen, A (University of North Bengal, 2009)
The pathogenesis related proteins are an important group of proteins produced in plants in response to infection by phytopathogens. The PR protein of Solanum tuberosum form an integral part of the host defence system. The unavailability of the crystal structure of the PR protein of Solanum tuberosum prompted us to undertake molecular modeling technique to look into the active sites and infer upon the structure function relationship. The model was built using I CFE as template. The functionality was studied. The model offers a reliable base to start X-crystallography and NMR based studies.
NBU Journal of Plant Sciences, Vol. 3, March-2009, pp. 15-19
Keywords: PR proteins; Solanum tuberosum molecular modelling; structure prediction; 3D model